Voltammetric Sensing in Portable and Point-of-Care Devices A Review of Recent Trends and Applications - Andi Eka Kartika (Hayyan Journal, 2025)
The growing demand for rapid, low-cost, and decentralized analytical technologies has driven the development of portable voltammetric sensors and point-of-care (POC) devices. This review examines recent advancements in miniaturized voltammetric systems, with a particular emphasis on innovations in screen-printed electrodes (SPEs), microfluidic integration, plug-and-play configurations, and smartphone-enabled electrochemical platforms. These technological developments exhibit substantial potential for real-time, on-site analytical applications across various fields, including medical diagnostics, environmental monitoring, food safety, and wearable health technologies. Several studies are highlighted to illustrate the practical implementation of voltammetric sensing, including glucose and uric acid detection, cancer biomarker analysis, heavy metal monitoring, pesticide screening, and nitrite and formaldehyde detection in food. The review also discusses major challenges such as signal noise, sensor stability, energy constraints, and the need for user-friendly interfaces. Finally, it outlines future research directions, focusing on the incorporation of artificial intelligence (AI), the Internet of Things (IoT), and low-power electronics to enable fully autonomous and smart diagnostic systems. These developments position voltammetric sensing as a vital tool in the future of accessible, real-time, and personalized analytical technologies.